Childhood environment and adulthood food addiction: Testing the multiple mediations of life history strategies and attitudes toward self. (1st March 2023) - Zhou, Hui; Wu, Anise M.S.; Su, Xiaoyu; Chang, Lei; Chen, Juliet Honglei; Zhang, Meng Xuan; Tong, Kwok Kit
Abstract: Food addiction is associated with both physical and mental health conditions, such as obesity and depression, and is considered a public health problem. Based on life history (LH) theory, this study aimed to test the association between unpredictable childhood environment and food addiction in adulthood and to examine LH strategies and attitudes toward self as psychological mediators of this association. A random sample of 1010 adults, aged from 18 to 88 years (44.8% male; M age = 38.52, SD age = 14.53), voluntarily participated in an anonymous telephone survey conducted in Macao, China. The results of a path analysis showed the significant and positive direct effect of childhood unpredictability on food addiction and its negative association with slow LH strategy, which in turn was negatively correlated with food addiction. In addition, slow LH strategy and self-judgment, rather than self-kindness, acted as serial mediators in the association between childhood unpredictability and food addiction. These findings support the applicability of LH theory to understanding food addiction, as well as pointing to the potential risk effect of self-judgment for food addiction in adulthood. Self-judgment reduction may be a potential supplementary approach for future food addiction intervention.